Lloyd Best : enduring relevance of independent thought, Caribbean freedom - Hall, Kenneth
Presents a collection of commentaries, essays and articles that represent close-up snapshots of the thoughts of the minds of some major thinkers on matters Caribbean. Includes some eulogies for, and tributes to, some notable Caribbean persons.